(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Iron oxide nanoparticles (Fe2O3NPs) were produced using the persimmons aqueous extract. The ability to produce pure Fe2O3NPs was demonstrated using the transmission electron microscope (TEM), field emission scanning electron microscope (FE-SEM), X-ray diffraction (X-ray), and fourier transform infrared spectroscopy (FTIR). In addition to being evaluated for antibacterial activity against both Gram positive and Gram negative bacteria, including Escherichia coli and Staphylococcus aureus, iron oxide NPs were also examined for anticancer activity against the hepatocellular carcinoma cancer (Hep-G2) cell line. Investigations into Fe2O3NPs considerable inhibitory efficacy against pathogenic bacterial strains revealed a wide range of biological uses for the particles.Furthermore, the Hep-G2 hepatocellular carcinoma cancer cell line is significantly cytotoxic to Fe2O3NPs. Consequently, the research demonstrates a minimal toxicity, making them suitable for use in a wide range of biological applications.